2014
DOI: 10.7205/milmed-d-14-00198
|View full text |Cite
|
Sign up to set email alerts
|

Highly Realistic, Immersive Training for Navy Corpsmen: Preliminary Results

Abstract: Highly realistic, immersive training has been developed for Navy corpsmen based on the success of the Infantry Immersion Trainer. This new training is built around scenarios that are designed to depict real-life, operational situations. Each scenario used in the training includes sights, sounds, smells, and distractions to simulate realistic and challenging combat situations. The primary objective of this study was to assess corpsmen participants' satisfaction with highly realistic training. The study sample c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…13,38 Moreover, results from the larger study of which this effort was a part showed significant increases in corpsmen's occupational and task-specific self-efficacy as well as in their perceived readiness as a result of participating in highly realistic medical simulation training. 29,39 Taken together, these findings suggest that training and other interventions aimed at increasing corpsmen's self-efficacy have the potential to improve resilience and readiness in this understudied population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…13,38 Moreover, results from the larger study of which this effort was a part showed significant increases in corpsmen's occupational and task-specific self-efficacy as well as in their perceived readiness as a result of participating in highly realistic medical simulation training. 29,39 Taken together, these findings suggest that training and other interventions aimed at increasing corpsmen's self-efficacy have the potential to improve resilience and readiness in this understudied population.…”
Section: Discussionmentioning
confidence: 98%
“…The data presented in this paper were collected as part of a larger study. 29 The goal of the larger study was to assess the effectiveness of "highly realistic training," a medical simulation training that corpsmen participated in while attending FMTB-West. The purpose of the training was to better prepare corpsmen to provide medical care in combat zones and other operational settings.…”
Section: Methodsmentioning
confidence: 99%
“…The cost of high-fidelity mass casualty incident simulation is significant. 34,35 Therefore, achieving valuable learning at low cost is a transferable benefit for any hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The Navy has only recently implemented the use of highly realistic training for corpsmen. To our knowledge, this project and a related project by our research team (Booth-Kewley & McWhorter, 2014) are among the first to implement and evaluate highly realistic training for Navy corpsmen. In light of evidence that highly realistic training has a positive impact on corpsmen, it may be beneficial to extend the training to other groups of military medical providers (e.g., physicians, nurses).…”
Section: Discussionmentioning
confidence: 99%